(untitled) (Journal of Applied Learning and Teaching, 2024)
One of the many visions of the National Education Policy 2020 (NEP, 2020), is to make efforts to internationalize the higher education system of the country. The purpose of internationalization is to make sure that like the universities from Europe, the US, Australia and other white-centric geopolitical locations of the world, the universities in India can attain global distinctions in terms of rankings, publications, curriculums and pedagogies. However, the execution process is plagued with flawed, superficial and grossly researched policies. To explain further, the initiatives for internationalizing the higher education systems are being undertaken at a rapid pace and in uncritical ways. For example, the focus of internationalization is centered on private universities, with not much focus on government-run institutions. In the name of student and faculty exchange programs, the universities in India are being flooded with white academicians whose physical visibility matters more than scholarliness. Their visibility on the university campuses is regarded as a potential marketing tool to initiate various forms of degree programs and motivate students to pay enormous amounts of registration fees. This opinion piece discusses how the project of internationalization of universities in India is engulfed with the phenomena of cargo cultism and whiteness syndrome. The arguments have been supported with personal conversations with two research participants from two private universities that are based in Noida and Hyderabad. Besides personal conversations, the arguments have also been supported by informal conversations with friends and colleagues and by analyzing photos, videos, and writings that are posted on social media by the university as markers of appreciation and success.